Grants Rating Due to Operative Public Procurement Law and by Applicable Regulations - Diószeginé Zentay, Éva (International Journal of Engineering and Management Sciences, 2017)
The aim of new Public Procurement law is to ensure the efficiency of appropriation public money. On new legal regulation public procurement procedures become significantly faster and transparency and competition is increasing. The law entered into force on the first of November in 2015, but has been modified several times since then. A year ago, the National Parliament adopted the law on State Program Evaluation cover. The legislation aims to make the European Union resources for projects in an objective, transparent and independent from the interests of the operators assessment system.